The Usability Construct: A Dead End?. (4th March 2018) - Tractinsky, Noam
Abstract : "Usability" is a construct conceived by the human–computer interaction (HCI) community to denote a desired quality of interactive systems and products. Despite its prominence and intensive use in HCI research, the usefulness of the usability construct to HCI theories and to our understanding of HCI has been meager. In this article I propose and discuss two reasons for this state of affairs. The first is that usability is an umbrella construct. Umbrella constructs are prevalent in scientific fields that are broad, diverse, and lack a unifying research paradigm. Accordingly, umbrella constructs, such as usability, tend to be vague and loose, characteristics that challenge our ability to accumulate and communicate knowledge and to capture real-world phenomena. The second reason involves the nature of the relations between the usability construct and its measures, a topic rarely discussed in HCI research. There appears to be a mismatch between how the HCI community has (implicitly) conceptualized these relations and how it has empirically examined them. The relations have been conceptualized according to a formative measurement model but have mostly been tested according to a reflective measurement model. The trouble is that representing the usability construct by the reflective model appears inappropriate, and representing it by the formative model involves considerable difficulties. Possible ways of addressing these issues are discussed, each with its advantages and drawbacks. I conclude that for scientific research on this subject to progress, the usability construct ought to be unbundled and replaced by well-defined constructs. The issues discussed in this article are relevant to other HCI umbrella concepts and constructs such as user experience.